The Effect of using stylistics of cooperative learning and circle learning in learning and rataning some skills of Artistic Gymnastics - Saleem, Sauzan (Journal of Physical Education, 2007)
The two research aims : 1. knowing the effect of using stylistics in learning and rataning some skills of artistic gymnastics. 2. To investigate which style in learning and rataning some skills of artistic gymnastics. Research procedures : Research program : experiment at program . specimen research : woman students of collage of sport education university of Baghdad – Al-Jadriaa – The one year – in department of sport training. Statistic treatment : Arithmetic mean – test (T) – test (F), Test (L.S.D) Conclusions : Make sure that the results of tests ore right for the suggested program of learning and the program of the sport college , also their effect on learning and retaining of skills of research